High-Throughput Screening Platform for Natural Product–Based Drug Discovery Against 3 Neglected Tropical Diseases: Human African Trypanosomiasis, Leishmaniasis, and Chagas Disease. (January 2015) - Annang, F.; Pérez-Moreno, G.; García-Hernández, R.; Cordon-Obras, C.; Martín, J.; Tormo, J. R.; Rodríguez, L.; de Pedro, N.; Gómez-Pérez, V.; Valente, M.; Reyes, F.; Genilloud, O.; et al.
African trypanosomiasis, leishmaniasis, and Chagas disease are 3 neglected tropical diseases for which current therapeutic interventions are inadequate or toxic. There is an urgent need to find new lead compounds against these diseases. Most drug discovery strategies rely on high-throughput screening (HTS) of synthetic chemical libraries using phenotypic and target-based approaches. Combinatorial chemistry libraries contain hundreds of thousands of compounds; however, they lack the structural diversity required to find entirely novel chemotypes. Natural products, in contrast, are a highly underexplored pool of unique chemical diversity that can serve as excellent templates for the synthesis of novel, biologically active molecules. We report here a validated HTS platform for the screening of microbial extracts against the 3 diseases. We have used this platform in a pilot project to screen a subset (5976) of microbial extracts from the MEDINA Natural Products library. Tandem liquid chromatography–mass spectrometry showed that 48 extracts contain potentially new compounds that are currently undergoing de-replication for future isolation and characterization. Known active components included actinomycin D, bafilomycin B1, chromomycin A3, echinomycin, hygrolidin, and nonactins, among others. The report here is, to our knowledge, the first HTS of microbial natural product extracts against the above-mentioned kinetoplastid parasites.